2012
DOI: 10.1021/la3025765
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Giant Pickering Emulsion and Colloidosome Droplet Interaction and Stability

Abstract: The interactions of two 2-mm pendant oil droplets grown in the presence of an aqueous solution of poly(glycerol monomethacrylate)-stabilized polystyrene latex particles was observed using a high-speed video camera. The coalescence behavior was monitored as a function of oil type (n-dodecane versus sunflower oil) and particle size (135 versus 902 nm), as well as in the presence and absence of an oil-soluble cross-linker [tolylene 2,4-diisocyanate-terminated poly(propylene glycol)]. The damping coefficient of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 51 publications
5
63
2
1
Order By: Relevance
“…The coalescence behavior of similar covalently cross-linked colloidosomes 69,70 has been investigated using a high speed video camera. Initially, Thompson et al 70 observed that individual millimetre-sized Pickering emulsion droplets prepared using poly(glycerol monomethacrylate)-stabilized latex particles readily coalesced when brought into contact.…”
Section: Giant/pendant Colloidosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The coalescence behavior of similar covalently cross-linked colloidosomes 69,70 has been investigated using a high speed video camera. Initially, Thompson et al 70 observed that individual millimetre-sized Pickering emulsion droplets prepared using poly(glycerol monomethacrylate)-stabilized latex particles readily coalesced when brought into contact.…”
Section: Giant/pendant Colloidosomesmentioning
confidence: 99%
“…Initially, Thompson et al 70 observed that individual millimetre-sized Pickering emulsion droplets prepared using poly(glycerol monomethacrylate)-stabilized latex particles readily coalesced when brought into contact.…”
Section: Giant/pendant Colloidosomesmentioning
confidence: 99%
“…34 With this method, a range of particles has been used from sterically-stabilized latex, 30,31,35,36 microgel particles, 33 silica 37 or metallic nanoparticles and epoxy resin microrods. 38 For example, we have used polystyrene latex particles synthesized by emulsion polymerization in the presence of a diblock copolymer stabilizer, where the water-soluble block is pH-responsive.…”
Section: Particle Crosslinkingmentioning
confidence: 99%
“…[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124] A hallmark of colloidosomes is their robust structure, as their building blocks are solid particles, which endow them with enhanced mechanical strength against coalescence. Another advantage associated with colloidosomes is that the permeability can be adjusted by changing the size of the particles.…”
Section: Colloidosomesmentioning
confidence: 99%